State Finances in India: A Case for Systemic Reform - Nirvikar Singh (2006)
This paper provides a self-contained overview of the present problems of state finances in India. It begins with an overview of historical evolution and current institutional structures, including economic, political, administrative and fiscal aspects of India's federal system. The paper then reviews the current situation of India's state government finances, going on to consider various developments that have shaped the states' current fiscal situation, including the roles of national economic reform, the intergovernmental transfer system, tax reform, and local government reform. Policy options for reforming institutions of fiscal federalism system, borrowing mechanisms for the states, and governance are then discussed, with an emphasis on the principle that states should have appropriate incentives for fiscal discipline at the margins of revenue and expenditure.